2022
DOI: 10.3390/cancers14061411
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status in Patients with Head and Neck Cancer before Radiotherapy: Baseline Description of an Observational Prospective Study

Abstract: (1) Background: The general hypothesis that HNC patients show compromised oral health (OH) is generally accepted, but it is not evidence-based. The objective of this baseline report of a prospective observational study was to describe the oral health of a cohort of patients with HNC at the time of dental evaluation prior to radiotherapy (RT). (2) Materials and Methods: Two hundred and thirteen patients affected by HNC who had received an indication for RT were examined with the support of orthopantomography (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
7
0
2
Order By: Relevance
“…With regard to oral health in different subsets of HNSCC patients, the results of the present study are in line with two previous studies, where the DMFT varied between 15 and 21 [1] or 16.2 and 18.3 [2], the number of edentulous patients varied between 0 and 37% [1], and the number of present teeth varied between 17.2 and 21.1 [2]. Due to different assessment criteria, the periodontal status cannot be directly compared across these studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to oral health in different subsets of HNSCC patients, the results of the present study are in line with two previous studies, where the DMFT varied between 15 and 21 [1] or 16.2 and 18.3 [2], the number of edentulous patients varied between 0 and 37% [1], and the number of present teeth varied between 17.2 and 21.1 [2]. Due to different assessment criteria, the periodontal status cannot be directly compared across these studies.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with head and neck squamous cell carcinoma (HNSCC) often present a poor oral health already at the time of diagnosis [1,2], which is then further reduced during radio (chemo)therapy [3,4]. Besides classical risk factors, such as tobacco exposure, alcohol abuse, or human papillomavirus (HPV) infection, several previous studies found poor oral hygiene or poor oral health status to be independent risk factors for HNSCC [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, limited information on the oral health of the specific group of OPSCC patients is available. In a recent study from Italy, the median DMFT of OPSCC patients amounted to 16, 82% of the patients were affected from periodontitis and only 2% were edentulous ( 1 ). Two studies from the UK reported a mean number of 19 to 22 present teeth, a DMFT of 15 to 17, and a moderate alveolar bone loss ( 4 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health is often compromised in patients with head and neck squamous cell carcinoma (HNSCC) (1)(2)(3)(4). Several previous studies found a positive association between poor oral health or poor oral hygiene and HNSCC (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Special attention is needed when further RT treatment is needed, considering the higher risk of oral sequelae. All patients are visited with the support of orthopantomography (OPT), and periapical radiographs, whenever possible, are performed to detect dental diseases 14,15 . First, anagraphic and anamnestic data were carefully recorded, particularly focusing on the oncologic history of the patient and on exposure to risk factors for oncologic and dental diseases.…”
Section: Methodsmentioning
confidence: 99%